Toward Interactive Dictation - Li, Belinda Z.; Eisner, Jason; Pauls, Adam; Thomson, Sam (ACL 2023, 2023)
Voice dictation is an increasingly important text input modality. Existing systems that allow both dictation and editing-by-voice restrict their command language to flat templates invoked by trigger words. In this work, we study the feasibility of allowing users to interrupt their dictation with spoken editing commands in open-ended natural language. We introduce a new task and dataset, TERTiUS, to experiment with such systems. To support this flexibility in real-time, a system must incrementally segment and classify spans of speech as either dictation or command, and interpret the spans that are commands. We experiment with using large pre-trained language models to predict the edited text, or alternatively, to predict a small text-editing program. Experiments show a natural trade-off between model accuracy and latency: a smaller model achieves 28% single-command interpretation accuracy with 1.3 seconds of latency, while a larger model achieves 55% with 7 seconds of latency.